2017
DOI: 10.1016/j.bjps.2017.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Donor site morbidity in DIEP free flap breast reconstructions: A comparison of unilateral, bilateral, and bipedicled surgical procedure types

Abstract: Although further research with greater statistical power will be valuable, the results of this investigation provide evidence that donor site morbidity of bipedicled DIEP free flap breast reconstructions does not increase when compared with those of unipedicled unilateral and unipedicled bilateral surgical procedure types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 22 publications
2
30
0
1
Order By: Relevance
“…Indeed, the incidence of fascial abdominal bulge and hernias has declined significantly since it has replaced the use of the TRAM flaps 7 . However, the incidence of abdominal bulging is still high and varies from 2.3% to 33% 8‐10 . Our incidence of 7% is well in line with these studies.…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, the incidence of fascial abdominal bulge and hernias has declined significantly since it has replaced the use of the TRAM flaps 7 . However, the incidence of abdominal bulging is still high and varies from 2.3% to 33% 8‐10 . Our incidence of 7% is well in line with these studies.…”
Section: Discussionsupporting
confidence: 75%
“…Figure 1 shows the inclusion process used in study selection, which identified 20 studies for final analysis. Table 1 presented the features [ 23 42 ] of included studies. All these studies were case-control in nature, including 3 prospective studies and 17 retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of previous studies compared uni- and bilateral breast reconstructions using DIEP flaps [ 15 , 16 ] or evaluated a single flap type for breast reconstruction, such as superior gluteal artery perforator (SGAP) flaps [ 17 , 18 ] or TMG flaps [ 6 ]. A cohort study comparing two large patient cohorts that underwent bilateral simultaneous reconstructions with either double DIEP or double TMG flaps has not been conducted so far.…”
Section: Discussionmentioning
confidence: 99%